Causes of mortality in neurofibromatosis type 2. (2nd January 2015) - Aboukais, Rabih; Zairi, Fahed; Bonne, Nicolas-Xavier; Baroncini, Marc; Schapira, Stéphane; Vincent, Christophe; Lejeune, Jean-Paul
Abstract: Object. The causes of mortality in neurofibromatosis type 2 (NF2) patients are poorly studied in the literature. Our study aimed to fit this gap by analyzing the main causes of death in this population. Methods. This study is the retrospective review of prospectively collected data of 80 patients with NF2 disease followed in Lille University Hospital between 1987 and 2011. Demographical data, diagnosis criteria, and cause of death were recorded. Results. There were 45 men and 35 women, with a mean age at diagnosis of 27.2 years (range: 6–73 years; SD: ± 15.4). Sixty-eight patients met Manchester criteria and the others had an identified mutation in the NF2 gene which confirmed the diagnosis. Of all patients, we noted 7 deaths. The mean age at diagnosis of dead patients was 26 years. The mean age of death was 38.9 years. The causes of death were suicide in 1 patient, hematoma after surgical removal of grade IV vestibular schwannoma in 1 patient, aspiration pneumonia after swallowing disturbances in 3 patients, intracranial hypertension related to growth of multiple meningiomas in 1 patient, and brachial plexus sarcoma grade 3 in the last patient. Conclusion. NF2 is a serious disease that can quickly be life-threatening. The presence of lower cranial nerves schwannomas is a poor prognostic factor, and radiosurgery should be considered for their treatment, as surgical removal often worsens the swallowing disturbances. A psychological support should also be provided.